The incidence of hypophosphatemia in the early posttransplant period in renal transplant recipients and its association with graft function - Isıktas Sayılar, Emel (The European Research Journal, 2021)
Objectives: To investigate the prevalence of posttransplant hypophosphatemia in the early posttransplant period among renal transplant recipients in relation to its impact on renal graft function. Methods: A total of 78 renal transplant recipients who were transplanted between January 2016 and March 2020 were included in this retrospective single center study. Data on laboratory findings (phosphate, creatinine, estimated glomerular filtration rate [eGFR], albumin, serum corrected calcium and parathyroid hormone [PTH] levels) at pre- and posttransplant 3 month follow up period were recorded. Results: Hypophosphatemia was detected in 16 (20.8%), 13 (16.7%) and 7 (9.1%) patients at the posttransplant day 10, month 1 and month 3, respectively. Posttransplant day 10 and day 30 measurements revealed significantly lower serum creatinine values (p < 0.001 and p < 0.07, respectively) and significantly higher eGFR values (p = 0.009 and p = 0.036, respectively) in the hypophosphatemic group compared to the normophosphatemic group. Serum phosphate displayed linear relationship with creatinine at day 10 (r=0.687, p < 0.001), day 30 (r=0.301, p = 0.007), while not correlated with PTH levels at posttransplant day 10, day 30 and day 90. Conclusions: Our findings suggest that hypophosphatemia is common in the early posttransplant period, particularly first month after kidney transplantation, being associated with better renal graft function.